2015
DOI: 10.1111/andr.12099
|View full text |Cite
|
Sign up to set email alerts
|

Adding liraglutide to lifestyle changes, metformin and testosterone therapy boosts erectile function in diabetic obese men with overt hypogonadism

Abstract: SUMMARYThe aim of this retrospective observational study was to evaluate whether adding liraglutide to lifestyle changes, metformin (Met) and testosterone replacement therapy (TRT), by means of improving weight and glycaemic control, could boost erectile function in type 2 diabetic obese men with overt hypogonadism and erectile dysfunction (ED) in a 'real-life setting'. Forty-three obese, diabetic and hypogonadal men (aged 45-59 years) were evaluated because of complaining about the recent onset of ED. They we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(73 citation statements)
references
References 72 publications
(144 reference statements)
2
69
0
2
Order By: Relevance
“…An animal study showed that EXE may have a beneficial effect on obese male fertility because of its good performance on losing weight (Zhang et al., ). In men complaining of erectile dysfunction with the coexistence of hypogonadism and T2D, the addition of liraglutide to T replacement therapy and MET regimen allows to achieve serum T levels in the range of healthy men, as well as to reach glycaemic target and to lower weight, leading to a considerable improvement of erectile dysfunction (Giagulli et al., ). In summary, EXE‐induced weight loss may be an important indirect reason for the increase in serum TT levels.…”
Section: Discussionmentioning
confidence: 99%
“…An animal study showed that EXE may have a beneficial effect on obese male fertility because of its good performance on losing weight (Zhang et al., ). In men complaining of erectile dysfunction with the coexistence of hypogonadism and T2D, the addition of liraglutide to T replacement therapy and MET regimen allows to achieve serum T levels in the range of healthy men, as well as to reach glycaemic target and to lower weight, leading to a considerable improvement of erectile dysfunction (Giagulli et al., ). In summary, EXE‐induced weight loss may be an important indirect reason for the increase in serum TT levels.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in a group of ten obese KS patients with T2D and erectile dysfunction (ED), the addition of metformin and liraglutide induced weight loss and improved erectile function in the patients in which TRT alone was insufficient to achieve serum T levels in the range of healthy men. Furthermore, the patients were able to reach glycemic targets and to lower weight, leading to a considerable improvement of ED [42].…”
Section: Insulin-resistance and Metabolic Syndrome In Klinefelter Synmentioning
confidence: 97%
“…However, given the fact that fat accumulation and distribution seems to plays a pivotal role in triggering metabolic abnormalities, drugs targeting body fat should be preferred. Although few data are available on the effect of hypoglycemic agents in KS, some drugs appear to be preferential [42,62]. In particular, metformin and GLP-1 receptor agonists should be the preferred drugs to use in KS patients with diabetes.…”
Section: Diagnostic and Therapeutic Perspectivesmentioning
confidence: 99%
“…The current data are controversial as they relate to diet, glycemic control and ED, with both positive and negative studies (36,(55)(56)(57). Based on these conflicting data, a prudent clinician should encourage optimal glycemic control as a potential factor in maintaining erectile function (36,58,59).…”
Section: Treatment Of Edmentioning
confidence: 99%